AKIELS Model Analysis of the Local Perfume Brand HMNS in Building Loyalty Through Digital Communication - Amadea Giovanni Calista; Irene Oinike Simanjuntak; Meliani Nurul Safitri (Jobmark: Journal of Branding and Marketing Communication, 2025)
The local perfume industry in Indonesia has witnessed a remarkable evolution, with local perfume brands making significant progress in the market. This article analyzes the distinctive success story of the HMNS brand through the AKIELS Model of Hierarchy of Branding lens. This comprehensive framework combines Brand Awareness, Brand Knowledge, Brand Image, Brand Experience, Brand Loyalty, and Brand Spirituality as critical elements. Through systematic exploration, this research aims to reveal the strategies the HMNS perfume brand used to build its unique identity and achieve success. Based on some exciting case studies, we reveal the branding strategy that has pushed HMNS to be at the forefront of the perfume industry. With a focus on building brand awareness, a positive brand image, a good brand experience, brand loyalty, and brand spirituality, we explore how HMNS differentiates itself in a competitive market, emphasizing the importance of cultural relevance and innovation.